The Development Learning Media Based Tutorials Video on Digestive System Practicum at SMAN 1 Ungaran - Handayani, Rima; Rudyatmi, Ely (Journal of Biology Education, 2020)
Implementation of biology practicums could not be carried out optimally. This is because students' skills in practicums are less, time allocation and media are limited, while the use of learning media is very important.. Digestive system practicums have 4 food tests and often make students confused, upside down between the chemical testers with one another, even though when the practical test food test material will be re-practiced and assessed as a practical value. For this reason, it is necessary to development of learning media based tutorial video on the digestive system practicum. The purpose of this research is to analyze the validity and feasibility of a learning media based tutorial video on the digestive system practicum. The research steps taken using the 4D development model are Define, Design, Development, and Disseminate. The research instruments used were media availability questionnaires, interview sheets, validity sheets, and teacher and student response questionnaire sheets. Analysis of the data used is descriptive quantitative percentage. The results showed tutorial video on the digestive system practicum was classified as very valid by media expert 98%, and material expert 100%. Tutorial video on the digestive system practicum is very feasible 97% according to the teacher and 10 students. In this research, the effectiveness of optimizing the digestive system practicum cannot be carried out due to the Covid 19 pandemic. It is recommended to test the effectiveness of the digestive system practicum tutorial video media in future research so that it can be applied in optimizing practicum in schools.